Inducing new secondary metabolites through co-cultivation of the fungus Pestalotiopsis sp. with the bacterium Bacillus subtilis. Issue 3 (18th January 2017) - Liu, Shuai; Dai, Haofu; Heering, Christian; Janiak, Christoph; Lin, Wenhan; Liu, Zhen; Proksch, Peter
Graphical abstract: Highlights: Two new lactones were isolated from the axenic culture of Pestalotiopsis microspora . Co-culture of this fungus with Bacillus subtilis yielded two new sesquiterpenoids. X-ray diffraction analysis was performed for the new zierane-type sesquiterpene. Abstract: Two new lactones, pestalotiolactones A (1 ) and B (2 ), together with three known compounds (3 –5 ) were isolated from the axenic culture of the endophytic fungus Pestalotiopsis sp., obtained from fruits of Drepanocarpus lunatus (Fabaceae). Co-culture of this fungus with Bacillus subtilis afforded two new sesquiterpenoids pestabacillins A (6 ) and B (7 ) as well as eight known compounds (8 –15 ). Their structures were elucidated by extensive analysis of the NMR and MS data as well as by comparison with literature data. All isolated compounds were evaluated for their cytotoxic and antimicrobial activities but proved to be inactive.